2015
DOI: 10.1021/jp511248q
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transitions of Poly(methyl methacrylate) Confined in Nanopores: Conversion of Three- and Two-Layer Models

Abstract: The glass transitions of poly(methyl methacrylate) (PMMA) oligomer confined in alumina nanopores with diameters much larger than the polymer chain dimension were investigated. Compared with the case of 80 nm nanopores, PMMA oligomer confined in 300 nm nanopores shows three glass transition temperatures (from from low to high, denoted as Tg,lo, Tg,inter, and Tg,hi). Such phenomenon can be interpreted by a three-layer model: there exists an interphase between the adsorbed layer and core volume called the interla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 68 publications
5
50
0
1
Order By: Relevance
“…Recently, many research groups have devoted attention to exploration of the effects of AAO nanoconfinement, which alters physical, chemical, and mechanical properties, on molecular dynamics, molecular orientation, morphology transformation , and so forth. Especially, nanoconfinement effects on various geometries have been reported to influence the thermal glass transition of amorphous polymers . In this work, we investigated the influence of AAO nanocylindrical confinement on thermal property of PS (PS2), the PS nanofiber array with 50‐nm diameter and 50‐µm length that is fabricated by imprint temperature 200°C, pressure 5.0 MPa, and press time 30 min was used to investigate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many research groups have devoted attention to exploration of the effects of AAO nanoconfinement, which alters physical, chemical, and mechanical properties, on molecular dynamics, molecular orientation, morphology transformation , and so forth. Especially, nanoconfinement effects on various geometries have been reported to influence the thermal glass transition of amorphous polymers . In this work, we investigated the influence of AAO nanocylindrical confinement on thermal property of PS (PS2), the PS nanofiber array with 50‐nm diameter and 50‐µm length that is fabricated by imprint temperature 200°C, pressure 5.0 MPa, and press time 30 min was used to investigate.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the DSC heating curves of PS film and PS nanofiber array, PS film with the 40 µm of thickness has T g about 100°C while the T g of PS nanofiber array has higher T g of 104°C. Increasing of T g of the PS nanofiber arrays caused by polymer chains were squeezed in AAO confinement led to increasing the polymer chain packing density, also increasing of T g . Especially during molten polymer solidification after imprinting, strong interfacial interaction of the molten polymer and the AAO wall engenders the close‐packed form of polymer chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer confinement in nanocomposites influences properties including the glass transition temperature ( T g ) of the polymer as well as the stiffness and viscoelastic behavior of the nanocomposites. Molecular polymer confinement can be achieved by filling polymer molecules into a nanoporous matrix with a pore size less than the bulk root‐mean‐square end‐to‐end distance of the polymer, which has been shown to reduce entanglements, form ordered morphology, influence T g , improve polymer diffusivity, and enhance fracture resistance of the nanocomposites .…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have employed DSC to investigate the T g -confinement behavior of polymer nanorods supported in anodic aluminum oxide (AAO) templates. 67,68,71 Li et al 67 reported that AAO-template-supported PMMA nanorods exhibited two T g 's, one higher and one lower than the bulk T g of the polymer. This was explained in terms of a two-layer model: polymer near the polymer-template interface possessed a higher T g due to attractive interactions 4 with the substrate, and polymer near the core of the nanorods possessed a lower T g due to poorer packing of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%